(untitled) (Journal of Engineering, 2014)
The Asphalt cement is produced as a by-product from the oil industry; the asphalt must practice further processing to control the percentage of its different ingredients so that it will be suitable for paving process. The objective of this work is to prepare different types of modified Asphalt cement using locally available additives, and subjecting the prepared modified Asphalt cement to testing procedures usually adopted for Asphalt cement, and compare the test results with the specification requirements for the modified Asphalt cement to fulfill the paving process requirements. An attempt was made to prepare the modified Asphalt cement for pavement construction in the laboratory by digesting each of the two penetration grade Asphalt cement (40-50 and 60-70) with sulfur, fly ash, silica fumes. Three different percentages of each of the above mentioned additives have been tried using continuous stirring and heating at 150 ºC for 30 minutes. The prepared modified Asphalt specimens were subjected to physical properties determination; the penetration, softening point, ductility before and after laboratory aging. It was concluded that all percentage of additives has reduced the penetration value of asphalt cement, an exception to that could be noticed when using asphalt cement (40-50) and when adding sulfur. Softening point was increased with the addition of all percentage of additives except that with 7% sulfur by wt. of asphalt cement (40-50) it decreased by 8%. After aging in general, the penetration decreased by about 37% for control specimens and the softening point increased by about 8% for control specimens. For asphalt cement 40-50 after aging, Sulfur has the least impact on ductility since it reduces it by 20%. Silica fumes have moderate effect on ductility when it reduces it by 35%, while fly ash shows the highest impact of 36%. For asphalt cement 60-70 after aging, sulfur was able to almost retain its ductility, while fly ash shows moderate reduction in ductility within a range of 20-36% and silica fumes shows high impact on ductility in the range of 30-50%.